Critical Foundations in Young Adult Literature - Garcia, Antero. author. aut Link
XX, 142 p.
Keywords: Young Adult literature, from The Outsiders to Harry Potter, has helped shape the cultural landscape for adolescents perhaps more than any other form of consumable media in the twentieth and twenty-first century. With the rise of mega blockbuster films based on these books in recent years, the young adult genre is being co-opted by curious adult readers and by Hollywood producers. However, while the genre may be getting more readers than ever before, Young Adult literature remains exclusionary and problematic: few titles feature historically marginalized individuals, the books present heteronormative perspectives, and gender stereotypes continue to persist. Taking a critical approach, Young Adult Literature: Challenging Genres offers educators, youth librarians, and students a set of strategies for unpacking, challenging, and transforming the assumptions of some of the genre's most popular titles. Pushing the genre forward, Antero Garcia builds on his experiences as a former high school teacher to offer strategies for integrating Young Adult literature in a contemporary critical pedagogy through the use of participatory media.